Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1471-4159.1993.tb03264.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Phosphatidyl‐CMP Is Not the Source of Diacylglycerol Accumulation Induced by Lithium in NG108‐15 Cells

Abstract: Previous studies have shown that in the neuroblastoma x glioma hybrid cell line NG108-15 lithium is able to induce an increase in diacylglycerol levels. This effect was shown to be enhanced by the presence of bradykinin. Another striking effect of lithium was a marked gain in the level of the liponucleotide phosphatidyl-CMP. Increased phosphatidyl-CMP levels were detected in the presence of lithium alone but were considerably more pronounced in the presence of both lithium and bradykinin. These results are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…CGCs is similar to previous observations by Drummond and Raeburn (1984) using GH3 pituitary cells (see also Brami et al, 1993) and may well arise due to the disruption by Li~of Ptdlns resynthesis, leading to accumulation of lipid intermediates. This conclusion is supported further by the effect of extracellular inositol (500 ‚uM), which reversed the Litenhanced DAG accumulation.…”
Section: The Enhancement Of Stimulated Dag Levels By Li~insupporting
confidence: 91%
“…CGCs is similar to previous observations by Drummond and Raeburn (1984) using GH3 pituitary cells (see also Brami et al, 1993) and may well arise due to the disruption by Li~of Ptdlns resynthesis, leading to accumulation of lipid intermediates. This conclusion is supported further by the effect of extracellular inositol (500 ‚uM), which reversed the Litenhanced DAG accumulation.…”
Section: The Enhancement Of Stimulated Dag Levels By Li~insupporting
confidence: 91%
“…The reduction in MARCKS content at the 1 mM LiCI concentration was most pronounced under muscarinic agonist stimulation and limiting inositol concentration. The potentiation of MARCKS downregulation observed on muscarinic receptor stimulation may be explained in part by a relatively greater depletion of intracellular inositol stores and the resultant CMP-PA and DAG accumulation observed in other cell systems (Drummond and Raeburn, 1984;Downes and Stone, 1986;Godfrey, 1989;Brami et al, 1991Brami et al, , 1993Sillence and Downes, 1992;Stubbs and Agranoff, 1993). Thus, the small reduction in MARCKS observed in cells under the resting state was only apparent under inositol-free conditions and was easily prevented with as little as 0.5 p.M inositol.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years several lines of investigation have lent support to this hypothesis. Numerous studies performed in various cell systems, in both cells and the brain, have demonstrated lithium-induced effects on the receptor-mediated P1 hydrolysis pathway, including decreased cellular inositol levels (Allison et al, 1976) and significantly elevated levels of IPs (Dixon et al, 1992;Sun et al, 1992;Atack et al, 1993;Ishima et al, 1993), CMP-PA (Godfrey, 1989;Kennedy et al, 1990;Watson et al, 1990;Atack et al, 1993;Stubbs and Agra-noff~1993;Jenkinson et al, 1994;Lenox and Watson, 1994), phosphatidic acid, and DAG (Drummond and Raeburn, 1984;Downes and Stone, 1986;Brami et a!., 1991Brami et a!., , 1993 (for review, also see Manji et al, 1995). The IC.~0 of lithium for IMPase (0.8 mM) is within the range (0.6-1.2 mM) of therapeutic plasma lithium levels required for treatment of affective disorders (Hallcher and Sherman, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…addition, several mammalian and human-based studies have linked DGKA function with epilepsy (Leach et al, 2007, Rodriguez de Turco et al, 2001 and bipolar disorder (Baum et al, 2007, Moya et al, 2010. Furthermore, DAG acts to regulate protein kinase C (PKC) activity that is also elevated during manic episodes (Wang and Friedman, 1996), and lithium is known to increase DAG levels (Brami et al, 1993). Thus, the molecular mechanism of VPA may be evolutionarily conserved from D. discoideum to mammals, through DGKA-dependent signalling.…”
Section: Bipolar Disorder Research In a Social Amoebamentioning
confidence: 99%